PROFIL PENGGUNA, TUJUAN PERJALANAN, DAN FAKTOR PENDORONG PENGGUNAAN OJEK ONLINE DI YOGYAKARTA - Muhammad Iqbal Habibi Kamal (LPPM Universitas Negeri Jakarta, 2021)
Abstract The phenomenon of the increasing number of online motorcycle-based ride-hailing (MBRH) users from year to year raises the hypothesis that this paratransit transportation service is the most common use by the Indonesian people in general. A few studies revealed that the characteristics of the ride-hailing user are younger, highly educated, and relatively higher income. Yogyakarta City Area (YCA) is a city of education that has a similar citizen characteristic, as mentioned before. This study aims to investigate the relation between socio-demography factors with the frequency of using motorcycle-based ride-hailing in YCA as alternative transportation modes used by the local citizen. This study uses a descriptive analysis method to explore the characteristic of ride-hailing user, trip destination and latent variable that affected of using motorcycle based ride-hailing. The result of this study showed that trip to airport/station is the most potential destination to use MBRH. In the other side, driver-friendly behavior is the most preferred factor for MBRH users in Yogyakarta Keywords: Motorcycle-Based Ride-Hailing, Socio Demography, Descriptive analysis